The unvanquished : the corrected text - Faulkner, William, 1897-1962 (Vintage Books, 1991)
Set in Mississippi during the Civil War and Reconstruction, the Sartoris family, who with their code of personal responsibility and courage, stands for the best of the Old South's traditions.